The Influence of People's Business Credit, Financial Literacy, and QRIS Use on the Income of Thrifting Traders at Medan's Melati Market - Hulu, Weli Yusliani; Faried, Annisa Ilmi; Suhendi , Suhendi (Universitas Dehasen Bengkulu, 2026)
This study aimed to examine the effects of the People’s Business Credit (Kredit Usaha Rakyat), financial literacy, and QRIS financial technology on business income among thrifting traders at Pasar Melati Medan. The population of this study consisted of 163 thrifting traders at Pasar Melati Medan, with a sample of 62 respondents selected using the Slovin formula and purposive sampling technique. This research was conducted in 2025. Data were collected through the distribution of questionnaires. The study employed primary quantitative data, which were processed using SPSS version 24.0 with an associative approach based on a multiple linear regression model. The results showed that the People’s Business Credit, financial literacy, and QRIS financial technology had positive and significant effects on business income, both partially and simultaneously, among thrifting traders at Pasar Melati Medan. The t-test results indicated that the People’s Business Credit had a regression coefficient of 0.426, a t-value of 5.221, and a significance level of 0.000. Financial literacy had a regression coefficient of 0.217, a t-value of 2.895, and a significance level of 0.005. QRIS financial technology had a regression coefficient of 0.234, a t-value of 3.184, and a significance level of 0.002. The F-test results showed an F-value of 216.329 with a significance level of 0.000. The People’s Business Credit was identified as the most dominant variable influencing business income, as it had the largest regression coefficient and t-value. Approximately 91.4% of the variation in business income could be explained by the People’s Business Credit, financial literacy, and QRIS financial technology, while the remaining percentage was influenced by other factors. Business income had a very strong relationship with the People’s Business Credit, financial literacy, and QRIS financial technology, as indicated by an R value of 0.958.